2020
DOI: 10.1186/s12950-020-00242-8
|View full text |Cite
|
Sign up to set email alerts
|

Urolithin a attenuates IL-1β-induced inflammatory responses and cartilage degradation via inhibiting the MAPK/NF-κB signaling pathways in rat articular chondrocytes

Abstract: Background: Osteoarthritis (OA) is characterized by inflammation and extracellular matrix (ECM) degradation and is one of the most common chronic degenerative joint diseases that causes pain and disability in adults. Urolithin A (UA) has been widely reported for its anti-inflammatory properties in several chronic diseases. However, the effects of UA on OA remain unclear. The aim of the current study was to investigate the anti-inflammatory effects and mechanism of UA in interleukin-1β (IL-1β)-induced chondrocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 47 publications
1
38
0
Order By: Relevance
“…MMP13 is a key enzyme responsible for the degenerative process in cartilage 36 . The inhibition of anabolic factor aggrecan and promotion of catabolic factor MMP13 indicate the degradation of extracellular matrix in cartilage tissues, which contributes to the cartilage injury in OA 37 . In this research, we found that extracellular matrix degradation was indeed caused via IL‐1β, revealed via the reduced aggrecan and increased MMP13.…”
Section: Discussionmentioning
confidence: 58%
“…MMP13 is a key enzyme responsible for the degenerative process in cartilage 36 . The inhibition of anabolic factor aggrecan and promotion of catabolic factor MMP13 indicate the degradation of extracellular matrix in cartilage tissues, which contributes to the cartilage injury in OA 37 . In this research, we found that extracellular matrix degradation was indeed caused via IL‐1β, revealed via the reduced aggrecan and increased MMP13.…”
Section: Discussionmentioning
confidence: 58%
“…UroA suppressed pro-inflammatory cytokines, including tumor necrosis factor alpha (TNFα) and interleukin 6 (IL6), decreased nitrite and inducible nitric oxide synthase (iNOS) production, by inhibiting the activation of NFκB signaling pathways [ 28 ]. Consistently, studies reported UroA’s ability to suppress the protein kinase B (Akt)/mitogen-activated protein kinase (MAPK) signaling pathways by either modulating the nuclear translocation of NFκB, inhibiting pro-inflammatory cytokine production, or reducing oxidative stress in various immune cells [ 28 , 29 , 30 , 31 , 32 , 33 ]. In supporting this notion, multiple research studies confirm UroA as a potent mediator to reduce inflammation associated with innate immunity and ROS production, as found in Table 1 .…”
Section: Current Status Of Knowledgementioning
confidence: 95%
“…Results showed that the MAPK and NF- κ B pathways were involved in the protective effects of urolithin A since this metabolite inhibited the phosphorylation of MAPK pathway members thus protecting chondrocytes against IL- β -induced inflammation injury. The overall conclusion of this study was that urolithin A is a promising possible therapeutic agent for the treatment of osteoarthritis [ 48 ]. Importantly, the results of this study confirmed those previously reported by Fu et al [ 49 ].…”
Section: Urolithin Activity In the Modulation Of Oxidative Stressmentioning
confidence: 99%